Selenium and clarithromycin loaded PLA-GO composite wound dressings by electrospinning method. Issue 12 (13th August 2022) - Ciftci, Fatih; Ayan, Sumeyra; Duygulu, Nilüfer; Yilmazer, Yasemin; Karavelioglu, Zeynep; Vehapi, Meyrem; Cakır Koc, Rabia; Sengor, Mustafa; Yılmazer, Hakan; Ozcimen, Didem; Gunduz, Oguzhan; Ustundag, Cem Bulent
Abstract: Diabetic wounds are very problematic wounds that have a high risk of infection. The healing process of wounds in diabetic patients is more complicated than others. Wound dressing preparation is one of the promising treatment modalities for repairing damaged tissues in diabetic patients. The aim of this study is to demonstrate the antibacterial effects of drug release of clarithromycin from poly(lactic acid) (PLA) nanofibers incorporated with selenium (Se) and graphene-oxide (GO) to reveal their wound healing potential. In the present study, optimized PLA was combined with graphene oxide (GO) with a concentration of 0.45 wt%, 1 wt%, 1.50 wt%, 2 wt%, 2.50 wt%, and 3 wt%, respectively, and the combination was produced by modified Hummers method. After that, optimized PLA/GO was incorporated with Se and clarithromycin with PLA with the percentage by weight of 1:1, nanofiber patches were successfully produced by the electrospinning technique. In vitro antibiotic test, cell culture tests (cytotoxicity test, cell adhesion, and in vitro wound healing assay), morphological analysis (SEM), molecular interactions between the components (FT-IR), tensile strength, and physical analysis (viscosity, surface tensile, density and conductivity tests) were carried out after production of nanofiber patches. According to the results, the average pore size of 8 wt% PLA + 1 wt% GO + 1 wt% Se + 1 wt% clarithromycin nanofiber is 640 nm. Moreover, 8 wt% PLA + 1 wt% GO + 1 wt% Se + 1 wt% clarithromycin has the highest viscosity and surface tension value than others with the values of 253.8 ± 6.67 mPas and 31.62 ± 2.13 mN/m, respectively. Finally, it was observed that Se-incorporated electrospun nanofibers had antibacterial effects and are highly promising wound healing materials. To sum up, the prepared nanofibers illustrated important suitable mechanical properties, controlled release and antibacterial effect and results showed that Se incorporated PLA-GO-drug composite is a promising wound healing material. Graphical Abstract: UF0001